2004
DOI: 10.2747/0020-6814.46.5.471
|View full text |Cite
|
Sign up to set email alerts
|

The Edaphic Factor in the Origin of Plant Species

Abstract: Although speciation has been a central focus in evolutionary biology for more than a century, there are very few case studies where we have a good understanding of the exact forces that may have acted in the diversification of a group of organisms. In order to examine such forces, botanists have often focused on closely related plants that are found under contrasting soil conditions. The study of such edaphically differentiated plants has provided valuable insight to the role of natural selection in evolution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(143 citation statements)
references
References 68 publications
2
135
1
2
Order By: Relevance
“…When slope, rock, and vegetation are discontinuous, the probability for speciation increases, as is evident in microevolutionary responses to heavy metals and serpentine endemism (32). The edaphic factor in the origin of plant species, including serpentine outcrops, mine tailings, guano deposits, and salt flats, are important in plant speciation (33). Hybrid sterility over tens of meters between ecotypes adapted to serpentine and nonserpentine soil was described by Moyle et al (11).…”
Section: Mitochondrial Genome In Adaptation and Incipient Ecological mentioning
confidence: 99%
“…When slope, rock, and vegetation are discontinuous, the probability for speciation increases, as is evident in microevolutionary responses to heavy metals and serpentine endemism (32). The edaphic factor in the origin of plant species, including serpentine outcrops, mine tailings, guano deposits, and salt flats, are important in plant speciation (33). Hybrid sterility over tens of meters between ecotypes adapted to serpentine and nonserpentine soil was described by Moyle et al (11).…”
Section: Mitochondrial Genome In Adaptation and Incipient Ecological mentioning
confidence: 99%
“…In spite of this, the magnesium effect seems to be dominant in our data set. It is generally known that serpentinite or dolomite bedrock drives evolutionary processes such as natural selection and speciation in vascular plants and ferns (Rajakaruna 2004), but there is insufficient evidence of this for bryophytes. Shaw (1991) found no evidence that serpentinite plants of Funaria flavicans were more tolerant of high Mg:Ca ratios or high nickel combined with a high Mg:Ca ratio.…”
Section: Magnesium Toxicity As An Evolutionary Trigger For Wetland Brmentioning
confidence: 99%
“…Magnesium-rich environments generally act as an important evolutionary trigger for vascular plants and ferns (Rajakaruna 2004, Kolář et al 2012, 2014a, Vicić et al 2014, but for bryophytes the evidence for serpentinite or dolomite ecotypes is poor (Shaw 1991). We aimed to advance the understanding of the genetic background of calciumtolerance in bryophytes by answering the following questions: (i) Will the significant genetic variation in S. warnstorfii reported by Mikulášková et al (2015) be confirmed using a new independent data set?…”
Section: Introductionmentioning
confidence: 97%
“…Special soil types-chemically distinctive and azonal soilsoften harbor high numbers of rare and endemic species because they are inhospitable to competing species (O'Dell and Rajakaruna 2011) or because the strong selective pressures they impose contribute to rapid speciation (Kay et al 2011;Rajakaruna 2004). Soils derived from limestone represent one of these special substrates; limestone was the first of the ''special soils'' to be recognized as floristically distinct and has received extensive study throughout the world (Kruckeberg 2002).…”
mentioning
confidence: 99%